Altered Brain Connectivity in Early Postmenopausal Women with Subjective Cognitive Impairment - Vega, Jennifer N.; Zurkovsky, Lilia; Albert, Kimberly; Melo, Alyssa; Boyd, Brian; Dumas, Julie; Woodward, Neil; McDonald, Brenna C.; Saykin, Andrew J.; Park, Joon H.; Naylor, Magdalena; Newhouse, Paul A. (Frontiers in Neuroscience, 2016)
Cognitive changes after menopause are a common complaint, especially as the loss of estradiol at menopause has been hypothesized to contribute to the higher rates of dementia in women. To explore the neural processes related to subjective cognitive complaints, this study examined resting state functional connectivity in 31 postmenopausal women (aged 50-60) in relationship to cognitive complaints following menopause. A cognitive complaint index was calculated using responses to a 120-item questionnaire. Seed regions were identified for resting state brain networks important for higher-order cognitive processes and for areas that have shown differences in volume and functional activity associated with cognitive complaints in prior studies. Results indicated a positive correlation between the executive control network and cognitive complaint score, weaker negative functional connectivity within the frontal cortex, and stronger positive connectivity within the right middle temporal gyrus in postmenopausal women who report more cognitive complaints. While longitudinal studies are needed to confirm this hypothesis, these data are consistent with previous findings suggesting that high levels of cognitive complaints may reflect changes in brain connectivity and may be a potential marker for the risk of late-life cognitive dysfunction in postmenopausal women with otherwise normal cognitive performance.